Developing a plasmid for surface display containing the recombinant E6 protein of human papilloma virus type 18 for expression in yeast Yarrowia lipolytica - Mohaddeseh Koohichapan; Solmaz Moniri Javadhesari; Farshad Darvishi Harzevili; Catherine Madzak (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: Human papillomaviruses (HPV) with more than 100 types are categorized as low-risk and high-risk types. Types 16 and 18 of the virus alone are involved in 70% of cervical cancers. Currently, development of recombinant proteins of HPV for vaccination or therapy purposes has attracted scientists. Therefore, the present study was performed aimed to construct a surface display plasmid encoding E6 protein of human papillomavirus type 18.Methods: The DNA fragment encoding E6 protein of HPV18 was amplified by nested-PCR using DNA of a HPV18 positive person as PCR template. Then, the amplified fragment was double digested with HindIII and SfiI and cloned into the surface display plasmid pINA1317-YLCWP110.Results: Cloning of E6 protein encoding gene fragment into pINA1317-YLCWP110 plasmid was confirmed using PCR and restriction endonuclease double digestion. Also, the results of Sanger sequencing of the recombinant pINA1317-YLCWP110-E6 plasmid and alignment to gene bank further ensured the sequence accuracy, cloning position and reading frame of the gene in the recombinant vector.Conclusion: DNA fragment encoding E6 protein of HPV18 was successfully cloned into surface display plasmid pINA1317-YLCWP110 in appropriate locus and frame. Altogether, the recombinant pINA1317-YLCWP110-E6 plasmid constructed in this study can be expressed in the yeast host Yarrowia lipolytica and the resulted E6 protein may be used as a prophylactic or therapeutic vaccine or molecular marker.